Crosstalk of liver immune cells and cell death mechanisms in different murine models of liver injury and its clinical relevance - Khan, Hilal Ahmad; Ahmad, Muhammad Zishan; Khan, Junaid Ali; Arshad, Muhammad Imran (Hepatobiliary & pancreatic diseases international, 2017)
Liver inflammation or hepatitis is a result of pluripotent interactions of cell death molecules, cytokines, chemokines and the resident immune cells collectively called as microenvironment. The interplay of these inflammatory mediators and switching of immune responses during hepatotoxic, viral, drug-induced and immune cell-mediated hepatitis decide the fate of liver pathology. The present review aimed to describe the mechanisms of liver injury, its relevance to human liver pathology and insights for the future therapeutic interventions. The data of mouse hepatic models and relevant human liver diseases presented in this review are systematically collected from PubMed, ScienceDirect and the Web of Science databases published in English. The hepatotoxic liver injury in mice induced by the metabolites of CCl4, acetaminophen or alcohol represent necrotic cell death with activation of cytochrome pathway, formation of reactive oxygen species (ROS) and mitochondrial damage. The Fas or TNF-α induced apoptotic liver injury was dependent on activation of caspases, release of cytochrome c and apoptosome formation. The ConA-hepatitis demonstrated the involvement of TRAIL-dependent necrotic/necroptotic cell death with activation of RIPK1/3. The α-GalCer-induced liver injury was mediated by TNF-α. The LPS-induced hepatitis involved TNF-α, Fas/FasL, and perforin/granzyme cell death pathways. The MHV3 or Poly(I:C) induced liver injury was mediated by natural killer cells and TNF-α signaling. The necrotic ischemia-reperfusion liver injury was mediated by hypoxia, ROS, and pro-inflammatory cytokines; however, necroptotic cell death was found in partial hepatectomy. The crucial role of immune cells and cell death mediators in viral hepatitis (HBV, HCV), drug-induced liver injury, non-alcoholic fatty liver disease and alcoholic liver disease in human were discussed. The mouse animal models of hepatitis provide a parallel approach for the study of human liver pathology. Blocking or stimulating the pathways associated with liver cell death could unveil the novel therapeutic strategies in the management of liver diseases.